MANAGEMENT OF MATHEMATICAL TRAINING OF FUTURE ECONOMISTS IN THE SYSTEM MOODLE - Ivashchuk, Olena V. (Educological discourse, 2015)
In article the question of increase of efficiency of teaching mathematics to students of economic specialties by attraction to educational process of the learning management system Moodle is investigated. The article contains an example of a distance course, the structure of which provides high-quality assimilation of a training material, the organization of communication and the management of activity of participants of a course, flexibility, availability and interactivity of training, a variety of forms of check and an assessment of knowledge, training in cooperation. The Moodle functions in the course of training are defined. The possibility of a combination of traditional methods of training with remote methods is investigated.